KOMPETENSI PEDAGOGIK GURU IPS BERSERTIFIKAT PENDIDIK DI SMP NEGERI 1 BANJARMASIN - Sania Sania (JURNAL SOCIUS, 2016)
The purpose of this research is to investigate: (1) The pedagogical competence of IPS certified teachers in SMP Negeri 1 Banjarmasin, (2) The factors affecting Social Studies certified teacher competence in SMP Negeri 1 Banjarmasin. The data collection techniques used were observation, interviews, and documentation. The results show that (1) There are still short comings of the pedagogic competence of certified social studies teachers in SMP Negeri 1 Banjarmasin. Of the seven pedagogical components, there are three components that are not maximally applied, among others are understanding the characteristics of students, lacking of learning activities that utilizes the use of ICT, problems in assessmentandevaluation referring to the2013 Curriculum;(2) Factors affecting pedagogic competence of certified social studies teachers in SMP Negeri 1 Banjarmasin are: a) Input factor; b) Nurturing problem of the certified social studies teachers in SMP Negeri 1 Banjarmasin by the Municipal Education Authorities and the Principal, and c). Internal problems of teachers. In realizing competent and professional teachers, alls take holders must play a role and show responsibility in fostering sustainable teacher professionalism.Keywords: Pedagogic Competence, Social Studies Teacher, Educator’s CertificateTujuan dari penelitian ini adalah untuk mengetahui: (1) kompetensi pedagogik guru bersertifikat IPS di SMP Negeri 1 Banjarmasin, (2) Faktor-faktor yang mempengaruhi Ilmu Sosial bersertifikat kompetensi guru di SMP Negeri 1 Banjarmasin. Teknik pengumpulan data yang digunakan adalah observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa (1) Masih kekurangan dari kompetensi pedagogik guru IPS bersertifikat di SMP Negeri 1 Banjarmasin. Dari tujuh komponen pedagogis, ada tiga komponen yang tidak maksimal diterapkan, antara lain memahami karakteristik siswa, kurang dari kegiatan pembelajaran yang memanfaatkan penggunaan ICT, masalah dalam penilaian dan evaluasi mengacu pada 2013 Kurikulum; (2) Faktor-faktor yang mempengaruhi kompetensi pedagogik guru IPS bersertifikat di SMP Negeri 1 Banjarmasin adalah: a) faktor input; b) Memelihara masalah guru studi bersertifikat sosial di SMP Negeri 1 Banjarmasin dengan Otoritas Pendidikan Kota dan Kepala Sekolah, dan c). masalah internal guru. Dalam mewujudkan guru yang kompeten dan profesional, semua pemangku kepentingan harus berperan dan menunjukkan tanggung jawab dalam membina profesionalisme guru berkelanjutan.Kata kunci: Pedagogik Kompetensi, Ilmu Sosial Guru, Pendidik Sertifikat